2018
DOI: 10.15829/1560-4071-2018-6-159-165
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Physical Trainings as Cardioprotection Method for Coronary Bypass Surgery

Abstract: Цель. Оценить эффективность и безопасность включения физических трени-ровок в программу преабилитации пациентов перед коронарным шунтирова-нием (КШ) в условиях искусственного кровообращения (ИК) с позиции кардио-протекции. Материал и методы. Включено 38 пациентов, рандомизированных на две группы в зависимости от программы преабилитации. Пациентам группы 1 (n=20, средний возраст 57,9±7,15 лет) на этапе преабилитации был проведен курс физических тренировок высокой интенсивности, в группе 2 (n=18, сред-ний возрас… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
5
0
3
Order By: Relevance
“…It is well known that short-term high-intensity interval training (HIIT) to moderate-intensity continuous training (MICT) have impact on improving cardiorespiratory fitness, markers of inflammation, and glucose control in previously inactive adults with elevated risk of developing type 2 diabetes [12]. That type of physical activity could be added to the program of patients' pre-rehabilitation programs before on-pump coronary artery bypass grafting (CABG) [13]. This result shows that cross country skiing could be successful physical activity in prevention this disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that short-term high-intensity interval training (HIIT) to moderate-intensity continuous training (MICT) have impact on improving cardiorespiratory fitness, markers of inflammation, and glucose control in previously inactive adults with elevated risk of developing type 2 diabetes [12]. That type of physical activity could be added to the program of patients' pre-rehabilitation programs before on-pump coronary artery bypass grafting (CABG) [13]. This result shows that cross country skiing could be successful physical activity in prevention this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Изучение особенностей психофизиологических показателей у пациентов, перенесших коронарное шунтирование, в зависимости от применения короткого курса физической преабилитации. Процедура проведения ежедневного курса аэробных физических тренировок на тредмиле подробно описана здесь [2].…”
Section: цель исследованияunclassified
“…Показано, что физические тренировки могут улучшить не только общее физическое самочувствие, но и способствовать положительным изменениям липидного профиля, реологии крови и гемодинамики, снизить массу тела и частоту пульса в покое [1]. Продемонстрировано, что проведение физиче- [2,3]. В исследованиях на лицах пожилого возраста было обнаружено, что повышение уровня физической активности, действуя как нейропротекторный механизм, может уменьшить снижение когнитивных функций и обеспечить защиту от деменции при нормальном старении [4,5].…”
Section: Introductionunclassified
“…It has been established that physical training (PhT) improves not only general physical wellbeing, but also contributes to positive changes in the lipid profile, hemorheology, and hemodynamics, resulting in decreased body mass and resting heart rate (Argunova et al, 2017). PhT has been shown to help recover the optimal level of physical activity and accelerate patients' adaptation to different loads in the early postoperative period of coronary artery bypass grafting (CABG) (Argunova et al, 2017(Argunova et al, , 2018Doyle et al, 2019). Recent studies focusing on the older population have found that increased physical activity can reduce cognitive decline and provide protection against dementia by acting as a neuroprotective mechanism in normal aging (Voss et al, 2013;Joubert and Chainay, 2018).…”
Section: Introductionmentioning
confidence: 99%